Watu Gilesan Jagung: Deskripsi, Eksistensi, Nilai Edukasi dan Rekomendasi Kebijakan Konservasi - Kalvin Edo Wahyudi; Supranoto Supranoto (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Watu gilesan jagung (the corn grinding stone) is a historical relic that had an important use in its time, namely for grinding corn kernels into corn rice or smaller grains. As technology develops, watu gilesan jagung are becoming obsolete. Some were even damaged or thrown away. In fact, watu gilesan jagung has symbolic values that are relevant for education. This research aims to describe, reveal the existence, outline symbolic values that are relevant for education and recommend conservation policies. The research approach used is qualitative. Data was collected using observation, interviews, FGD and document collection techniques. Data analysis uses interactive models and the validity of the data is tested using triangulation. The research results show several important things. First, watu gilesan jagung has a unique description/profile and is different from other relics. Second, the existence of watu gilesan jagung is considered threatened, because many are thrown away, damaged or removed because they are considered unusable. Third, watu gilesan jagung has values that are relevant to education, namely the value of religiosity, social values and the value of struggle. Apart from that, there is also learning potential that can be applied, namely appropriate technology and character education. Fourth, for conservation policy recommendations, we suggest that watu gilesan jagung can be registered as a cultural heritage object. However, if this recommendation is not acceptable, we propose another conservation policy recommendation, namely an integrated approach, including integration with education, tourism, community and social media.